Transmission of Q-signaling by the tunneling procedure in the automatic telephone network of integrated services of the Serbian Armed Forces - Svrzić, Slađan M.; Boyanov, Yulijan K. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: To specify the practical application of ECMA-355 and ECMA-336 Standards for Q-SIG tunneling and the implementation of mapping functions via the existing IP (Internet Protocol) network of the Serbian Armed Forces (Intranet SAF), in the Private Automatic Telephone Network SAF (PATN SAF), as the main part of the Private telecommunication-information networks of integrated services SAF (PISN SAF). Methods: Description of the implemented solution and analysis of the software parameters of the established transmission SIP route, with the display of the results obtained in the fight with jitter and echo in the network. Results: With such a solution, it was achieved that participants from the peripheral parts of the PISN SAF, which operate on the principle of transmission and circuit switching by TDM (Time Division Multiplexing), can connect with each other via the newly established central IP network SAF (Core network) which operates on the principle of transmission and switching packets with the SIP (Session Initiation Protocol), without losing the functionality of Q-SIG from the framework of the digital telecommunication network of integrated services ISDN (Integrated Services Digital Network). Conclusion: The article deals with the modern IP PINX (Private Integrated Services Network Exchange) manufactured by Mitel, type MX-ONE Service Node 6.0, which is implemented at the transit level PATN SAF and which successfully implements the process of tunneling Q-SIG through the IP network and the necessary functions for mapping the transmission of tunneled Q-SIG messages and mapping voice (and other audio) information to VoIP (Voice over IP) communication media streams through that network. Also, the basic elements for its software preparation during the introduction of a new SIP route, with a capacity of 30 IP trunks in a transmission beam realized with 100 Mb/s-T Ethernet, are given, and the fight with the present jitter and echo in the network is described. Finally, the paper presents the experience-based values ​​of the parameters for reducing the influence of jitter and suppressing echo.